A balanced view of casein interactions. (March 2017) - Horne, David S.
Abstract: In this short review of hydrophobicity in relation to the caseins and their properties, it is concluded that the scales are weighted heavily in favour of hydrophobic interactions contributing the attractive component in casein self-assembly and casein micelle formation. Multiple clusters of hydrophobic residues are identified as potential reaction sites in the hydrophobic tails and trains of the casein proteins. Multiple examples of the involvement of hydrophobic interactions are listed. The concentration of electrostatic charge in the phosphoserine clusters of the proteins amplifies the range of electrostatic repulsion. The cooperative, concerted nature of the phenomenon takes hydrophobic interaction to a similar operating range to provide the perfect foil to the repulsion. Graphical abstract: Highlights: The concept of hydrophobicity is reviewed. Clusters of hydrophobic residues are identified in the caseins. Casein interactions are shown to be a balance of electrostatic repulsion and an attractive component. Hydrophobic interactions are considered as a complex, concerted phenomenon. Multiple examples of hydrophobic interactions between the caseins are listed.